Thrombosis and Thromboembolic Complications in Fontan Patients: A Literature Review. (July 2014) - Firdouse, Mohammed; Agarwal, Arnav; Chan, Anthony K.; Mondal, Tapas
Hemodynamic fluctuations and thromboembolic complications are significant areas of concern during the postoperative management of patients with univentricular hearts. The objective of this study is to review the incidence and risk factors associated with thrombosis and thromboembolic complications following total cavopulmonary anastomosis, the third stage of the palliative surgical procedure. A literature search of published evidence was conducted on OvidSP MEDLINE(R) and Embase followed by paired title, abstract, and full-text screening based on specific inclusion criteria. High risks of thromboembolic outcomes were identified across studies, with variable incidences between 3% and 20%, high mortality rates up to 38%, and an inverse relationship with prophylaxis treatment administration. Several risk factors for thrombotic complications, including chronic systemic venous hypertension, protein-losing enteropathy, passive blood flow, atrial arrhythmias, conduit stenosis, prosthetic material use, coagulation factor abnormalities, and several patient characteristics were identified. Based on these findings, a prophylactic anticoagulation algorithm has been proposed.